VITAMIN D — THE IMPACT ON DEVELOPMENT AND TREATMENT OF ATRIAL FIBRILLATION - Julianna Zielska; Eliza Gawron; Paweł Liszka; Aleksandra Kaniak; Kacper Forszt; Adrianna Pielech; Ewa Turczyn; Julia Andrzejewska; Dominika Ziółkowska; Agata Ogórek (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Atrial fibrillation is the most common cardiac arrhythmia affecting approximately 700 thousand Polish people. In Poland, insufficient vitamin D levels are highly prevalent and concern around 90% of the population. Except the established, modifiable risk factors of AF, new risk factors such as vitamin D deficiency are being described. Some potential mechanisms involving vitamin D in atrial fibrillation pathogenesis include: cardiac remodelling via the vitamin D receptor, modulation of renin-angiotensin-aldosterone system, influence on parathyroid hormone concentration, changes in action potential duration and left atrium contractility, and activation of proinflammatory pathway by low vitamin D levels.Aim of the study: This review aims to analyze the potential relationship between vitamin D concentration and the risk of developing atrial fibrillation based on the current state of knowledge (as of 2025). Moreover, we tried to examine how vitamin D concentration could influence the efficacy of atrial fibrillation treatment methods such as cardioversion or ablation.Material and Methods: This review is based on literature from 2011 to 2024, searched in PubMed, Google Scholar, mp.pl and ClinicalTrials.gov that was describing the results of vitamin D deficiency on atrial fibrillation development and the treatment outcomes.Conclusions: Serum vitamin D concentration may have an impact on both atrial fibrillation onset and its treatment. It is possible that there are several groups of patients among whom the sufficient vitamin D level would be particularly beneficial. Further studies, especially those focusing on vitamin D supplementation, are needed to clarify the role of vitamin D in atrial fibrillation pathogenesis and treatment.